Последний поклон: [повесть в рассказах] - Астафьев Виктор Петрович (1992)
Экземпляры: аб. (1993) / Инвентарный номер: 36131 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: А 91Т. 3 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44